Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Dinas Pendidikan DKI Jakarta: The Effect of Work Motivation and Work Discipline on the Performance of Employees of the DKI Jakarta Education Agency - Yosivina Yosivina; Sofyan Marwansyah (CV Warnak Johanna Nusantara, 2025)
This study aims to determine the effect of work motivation and work discipline on employee performance at the DKI Jakarta Education Office. This research is quantitative research. The data used in the study are primary data collected through questionnaires using probability sampling techniques with the type of sample, namely simple random sampling. The population in this study were 30 employees of the DKI Jakarta Education Office. The sample in this study were 30 employees who were sampled. Data analysis was performed using multiple linear regression analysis using statistical product and services solutions (SPSS) software version 26: (1) Partially, motivation has no significant effect on employee performance, while work discipline affects employee performance; (2) Simultaneously, the results show that motivation and work discipline have a positive and significant effect on employee performance.